Demonstrating biosimilar and originator antidrug antibody binding comparability in antidrug antibody assays: a practical approach. (September 2017) - Ryding, Janka; Stahl, Michael; Ullmann, Martin
Biosimilar drug development has brought new challenges to bioanalytical ligand-binding assays used to determine drug concentration, antidrug antibodies and neutralizing antibodies. One particular challenge is how to demonstrate that the antidrug antibody assay can adequately detect antibodies against both biosimilar and originator. In this paper, we review the current guidelines and literature for practical recommendations and present a gap analysis. Case examples of antibody binding comparability testing are presented, and the challenges and implications are discussed. Based on the lessons learned from our biosimilar assay applications, we recommend a bioanalytical comparability testing approach that is outlined and discussed.